The Structure of Social Personality in Young Horses - Riihonen, Veera (My University, 2021)
In this study I aimed to understand the structure of young horses’ social personality towards humans and conspecifics, respectively. The study population consisted of 19 horses under four years old. I tested their sociality towards humans and their general reactivity to novelty with six different personality tests. The tests were conducted twice with six months in-between. Additionally, I assessed their sociality towards other horses by focal observations. I found two repeatable and context independent factors from the personality test data in which the variable loadings presented some overlap. The first factor, Reluctance, informs about the motivation of the horses to co-operate with humans, and the second factor, Unfocusedness, informs about their general interest towards humans. While I did not formally test whether the observational variables comply with the personality criterion, the sociality towards other horses seems to form one clear factor, Sociability; more social horses seek and are sought by other horses more regularly and are less aggressive towards other horses. There was no connection between either Reluctance or Unfocusedness and Sociability or any of the observed social behaviour variables tested on their own. I conclude that horses do have social personality factors for both human and horse sociality, but these are separate from each other. This separation of sociality aspects sheds light on the effects of domestication on sociality overall. The results call for more studies on differences in animal personality towards humans and conspecifics both in horses and other species with different management systems and domestication histories.
Keywords: social personality, personality structure, horse personality, domestication